Evaluation of different genotypes of mustard against Orobanche aegyptiaca - Gulwaiz Akhter; Tabreiz Ahmad Khan (Journal of Oilseed Brassica, 2026)
Among the major weed groups that cause huge economic losses to important cropping systems, Orobanche species aregreatly devastating. Egyptian broomrape (Orobanche aegyptiaca) is a parasitic weed causing major yield loss in manyfield and vegetable crops and is a serious threat to Indian mustard. In this study, several varieties of Indian mustardscreened in order to identify resistant genotypes. In the greenhouse conditions, genotypes were different in the degreeof susceptibility to Broomrape. Attachment number, emergence number, and dry matter of parasitic broomrapes wasaffected by biomass of genotype. A significant impact of the parasitism onto the dry weight of all infected mustardgenotype with variable degree was observed. Broomrape attachment was observed in all the cultivated genotypes withPusa mustard 24 being the most susceptible with the greatest number of emerged Orobanche shoots. In contrast, noemergence shoots were observed in four out of the fifteen genotype viz., Pusa Jaikisan, Pusa bold, Pusa Vijay and Pusamustard 26 which have less of attachment number and emergence number successively appear interesting for ourobjective.